Health Care Worker Burnout During the COVID-19 Pandemic in HIV Clinics in Guangxi, China: A Cross-sectional Analysis of Risk and Protective Factors. (12th May 2022) - Qiao, Shan; Sun, Shufang; Tam, Cheuk Chi; Li, Xiaoming; Zhou, Yuejiao; Shen, Zhiyong
Abstract: Dual epidemics of coronavirus disease 2019 (COVID-19) and HIV cause burnout among HIV health care workers. Guided by a socioecological framework, we investigated risk and protective factors of their burnout in Guangxi, China based on an online survey ( N = 1, 029) from April to May 2020. Descriptive and bivariate analyses and hierarchical regression were conducted. COVID-19–related stressors ( B = 0.648 [0.482–0.816], p < .001), challenges while delivering HIV services ( B = 0.236 [0.174–0.298], p < .001), and working in province/city-level institutes ( B = 2.302, [0.828–3.776], p =.002) were risk factors. Protective factors were resilience ( B = −0.596 [−0.687 to −0.504], p < .001), workplace social support ( B = −0.410 [−0.717 to −0.044], p =.03), and institutional responsiveness to COVID-19 ( B = −0.138 [−0.205 to −0.071], p < .001), respectively. Burnout-related interventions may benefit from promoting resilience, creating a supportive work environment, and strengthening institutional response to public health emergencies.